Self-affirmation and physical activity messages. (March 2020) - Strachan, Shaelyn M.; Myre, Maxine; Berry, Tanya R.; Ceccarelli, Laura A.; Semenchuk, Brittany N.; Miller, Cindy
Abstract: We examined the effects of a self-affirmation intervention in conjunction with message frame on attentional bias toward physical activity messages, and explicit psychological and behavioral responses to these messages. Inactive participants (N = 153) completed either a self-affirmation or a control task, were told they were not active enough for health benefits, then read either a gain or loss-framed message, followed by an attentional bias task and questionnaires measuring message processing, psychological reactions and behavior. One week later, participants completed an on-line measure of physical activity. Message frame did not moderate the self-affirmation effect. Self-affirmed participants reported slightly higher self-efficacy for exercising in the future and slightly lower, but not significant, perceived threat than participants in the control group. Self-affirmation and messages may need to be further supplemented with more intense interventions accompanied with adequate resources to facilitate intentions for and actual behavioral change for a complex behavior like physical activity. Highlights: Self-affirmation did not influence attentional bias to health threat words. Gain and loss frame messages did not differentially influence message response. Self-affirmation leads to higher self-efficacy than no affirmation. Neither self-affirmation nor message frame influenced physical activity behavior.